1970
DOI: 10.1113/jphysiol.1970.sp009108
|View full text |Cite
|
Sign up to set email alerts
|

The relation between carotid body chemoreceptor discharge, carotid sinus pressure and carotid body venous flow

Abstract: SUMMARY1. Activity in forty-two single chemoreceptor afferent fibres from the carotid body in thirty-nine cats was measured when the carotid body was naturally and artificially perfused. In nine of these cats, carotid body venous flow was also measured.2. When pressure within the carotid sinus segment was suddenly raised or lowered, chemoreceptor activity changed in the opposite direction within the first 5-10 sec by an amount which was significantly greater than the variation of activity in the control period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 17 publications
2
56
1
1
Order By: Relevance
“…in our experiments. However, although we cannot entirely preclude such a vascular mechanism, we consider it unlikely because moderate alterations in carotid blood flow do not cause sustained changes in chemoreceptor discharge (Biscoe, Bradley & Purves, 1970) and, in any event, chemoexcitation induced by ouabain was still manifest after stopping the infusion, even though any vascular effects of ouabain would have terminated (Treat et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…in our experiments. However, although we cannot entirely preclude such a vascular mechanism, we consider it unlikely because moderate alterations in carotid blood flow do not cause sustained changes in chemoreceptor discharge (Biscoe, Bradley & Purves, 1970) and, in any event, chemoexcitation induced by ouabain was still manifest after stopping the infusion, even though any vascular effects of ouabain would have terminated (Treat et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of altering the volume of venous return upon respiration was probably first documented by Krogh & Linhard (1913) and subsequently confirmed by Bouckaert & Pannier (1942), Yeomans, Porter & Swank (1943), Mills (1944 and Brown, Goei, Greenfield & Plassavas (1966). Respiration has also been shown to be affected by intravenous infusion (Harrison, Harrison & Marsh, 1932;Coleridge & Linden, 1955;Hirsch, Boyd & Katz, 1964) while more recently, Wasserman et al (1974) have shown that an increase in cardiac output induced by electrical pacing or by isoproterenol is associated with hyperpnoea and that beta-adrenergic blockade causes hypopnoea (Brown, Wasserman & Whipp, 1976 (Lipski, McAllen & Trzebski, 1976), an action which will be enhanced by activation of arterial chemoreceptors which are sensitive to small, transient changes in perfusion pressure (Lee, Mayou & Torrance, 1964;Biscoe, Bradley & Purves, 1970) and possibly potentiated centrally (Heistad, Abboud, Mark & Schmid, 1974 Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly increasing blood pressure causes decreased ventilation, whereas decreasing blood pressure causes increased ventilation. While these ventilatory effects were at one time attributed to increased or decreased perfusion of the arterial chemoreceptors (26,32), subsequent investigations in experimental preparations have shown that exclusion of the carotid body from the carotid sinus area does not alter the ventilatory response in vagotomized dogs (7) and sinoaortic denervation eliminates the pressuresensitive ventilation response in dogs (47), whereas the carotid body chemoreceptor in cats is insensitive to blood pressure change (3).…”
Section: Baroreceptors; Ventilation; Blood Pressurementioning
confidence: 99%